A framework for selection of global in-house centres outsourcing destinations in India. (1st June 2021) - Mittal, Amit; Chand, Pawan Kumar; Rahul, Aditya
The purpose of this paper is to examine the relative competitiveness of major Indian information technology hubs, namely Bangalore, Hyderabad and Pune. The comparison is based on key factors, namely manpower, technology, social, hedonistic, industrial-site, economic and governmental in the selection of global in-house centres for information technology and information technology enabled services [GIC (IT/ITES)] outsourcing destinations in India. The research study is based on a descriptive research design based on a purposive survey of 387 employees working in GICs (IT/ITES) in India. Data was collected by administering a structured questionnaire and analysed using structure equation modelling. The findings of the study which are drawn from a comparison among Bangalore, Hyderabad and Pune indicate that Bangalore is still the highest rated destination followed by Hyderabad at second place and Pune at third position in the selection of the most preferred location for GICs (IT/ITES) in India.